ARBITRAGEM LABORAL: O COMPROMISSO ARBITRAL COMO POSSIBILIDADE PARA A EFETIVAÇÃO DO ACESSO À JUSTIÇA - MONTEIRO, SASKYA (2023)
The present work aims to analyze the adoption of the arbitration procedure in the field of labor law regarding individual disputes, providing a historical, legislative, and bibliographic analysis. In order to meet the expectations of this study, a national and international historical overview of arbitration was presented, along with the established principles of labor law. Additionally, the adoption of the multi-door courthouse system in Brazil and its stimulation within the Brazilian scope were also examined. This analysis revealed that the Labor Reform brings greater difficulties to workers' access to justice, particularly by limiting the access to an efficient multi-door courthouse system to individuals with better economic conditions. In this context, the observed problem that is subject to analysis can be summarized in the following question: is the adoption of an arbitration procedure, as provided by the Labor Reform, effective and compatible in guaranteeing both material and non-material rights of workers in their diagonal relationship with employers? In order to address this question, an analysis of the arbitration procedure was carried out in accordance with the terms of the Labor Reform, with the main objective being the guarantee of material and non-material rights. To achieve this goal, a primarily hypothetical-deductive approach was used, establishing a comparison between the Labor Reform, the current adoption of the arbitration procedure, and its application from the perspective of the arbitration agreement. It is worth noting that the comparative method was employed in the procedural approach due to the investigation of differences and similarities between the conditions imposed by the Labor Reform and the functioning of the Judiciary in promoting access to justice. Consequently, it was found that the application of arbitration in individual disputes is possible, as long as certain aspects are respected, such as the termination of the employment contract and the subsequent removal of subordination, the arbitration agreement, and respect for the vulnerability of the worker